A Systematic Literature Review of Perceived Educational Quality as a Driver of Higher Education Intention - Riski Baroroh; Elly Purwanti; Dwi Priyo Utomo; Widayat Widayat; Eny Mayasari; Darman Syah Pulungan (West Science Journal Economic and Entrepreneurship, 2026)
This study aims to synthesize the existing literature on the role of perceived educational quality in shaping higher education intentions. A Systematic Literature Review (SLR) approach based on the PRISMA framework was employed. A total of 155 articles were identified, and 78 articles published between 2020 and 2025 met the inclusion criteria and were analyzed. The findings indicate that perceived educational quality is a multidimensional construct consisting of teaching quality, service quality, institutional reputation, academic environment, student–faculty interaction, and graduate employability, all of which contribute to students’ intentions to pursue higher education. The review further reveals that previous studies have produced inconsistent findings regarding the most influential dimensions of educational quality, resulting in fragmented theoretical understanding. This study addresses this gap by providing a comprehensive synthesis of the existing evidence and identifying key dimensions that consistently influence higher education intentions across different contexts. The findings contribute to the development of a more integrated conceptual framework and offer practical insights for higher education institutions in designing effective recruitment, marketing, and student retention strategies.